Articulation of the national policies of Peru with the digital transformation via the State Policy 35: a pending task - Amado Asenjo, Camilo (2024)
The objective of this research was to evaluate the articulated planning for the digital transformation, specifically of the Peruvian State Policy 35 [PE35], in the national policies (sectoral and multisectoral) of Peru. For this, the methodology was qualitative in approach, interpretive in design, and descriptive in level. The data came from the vertical alignment subchapters or annexes of the policies studied. The method was documentary analysis, instrumentalized by an analysis sheet. It was determined that only the Ministry of Agriculture and the Ministry of Defense were fully aligned with the digital transformation; that the Presidency of the Council of Ministers and the Ministry of Economy and Finance, only half; and that the Ministry of Production, the Ministry of Labor and Employment Promotion, the Ministry of Health, and others, did not even have a policy aligned with the PE35. It was concluded that there is a gap in the articulation of Peruvian national policies with the digital transformation, through the PE35.